254 Evaluation of Different Corn Milling Methods for High-moisture and Dry Corn on Finishing Cattle Performance and Carcass Characteristics. (7th May 2021) - Coulson, Caitlin A; Troyer, Braden; McPhillips, Levi J; Norman, Mitch; Erickson, Galen E
Abstract: Steers (n=600; Initial BW = 402 ± 17 kg) were fed for134 day to evaluate the effect of milling method and corn type on performance and carcass characteristics. Treatments were evaluated as a 2 × 3 factorial with factors being milling method (Automatic Ag® roller mill or hammer mill) and corn type (100% high-moisture, 100% dry, or 50:50 blend of high-moisture and dry corn). High-moisture corn was processed at harvested based on respective treatment and ensiled until trial initiation. Both dry corn and HMC were processed using a 16-mm screen in the hammer mill and the roller mill was adjusted to ensure all kernels were broken. There were no interactions between milling method and corn type for final BW, daily gain (ADG), or dry matter intake (DMI; P ≥ 0.32), but there was a tendency for an interaction for G:F (P = 0.09). Cattle fed 100% high-moisture corn processed with the Automatic Ag roller mill were 4.7% more efficient (P ≤ 0.01) with 55% lower fecal starch (P < 0.01) compared to high-moisture corn processed with the hammer mill. Cattle fed dry corn tended (P = 0.07) to have a greater live final BW regardless of milling type and had the greatest DMI (P ≤ 0.01) Intake decreased as high-moisture corn was increased in the diet. Due to no differences in ADG with lower DMI led to a 6% improvement (P ≤ 0.01) in G:F for steers fed HMC. There were no further effects (P ≥ 0.14) on performance or carcass traits regardless of milling method or corn type. Processing high-moisture corn using Automatic Ag roller mill improved feed efficiency compared to processing with a hammer mill when corn was included at 70% of the diet, but processing method had little effect when fed as dry corn or blended diets.